Trichoderma species’ in vitro and in planta inhibition against Ganoderma Boninense, a causative agent of basal stem rot in oil palm (Elaeis guineensis) - Jumiati Asis; Nur Aainaa Hasbullah; Mohamadu Boyie Jalloh; Noor Khairani Mohamad Basri; Palanivell Perumal; Peter Mojiun; Mohd. Rashid Mohd. Rakib (Sarhad Journal of Agriculture, 2024)
Trichoderma species are well-known biological control agents (BCAs) that have significant antagonistic activity against various fungal phytopathogens. On the other hand, Ganoderma boninense has been identified as the phytopathogen causing basal stem rot (BSR), a devastating disease in oil palm crop (Elaeis guineensis). In this study, the in vitro and in planta inhibition of G. boninense using Trichoderma isolates were evaluated. A total of 20 Trichoderma isolates were collected. Among the isolates, T4RH and T8R were selected for further in planta experiments as they showed significant inhibitory activity against G. boninense via in vitro dual-culture and dual-plate assays. Isolates T4RH and T8R were identified as Trichoderma virens and Trichoderma asperellum by the internal transcribed spacer gene sequences. The in-planta experiment was conducted by inoculation of 3-month-old oil palm seedlings with rubber wood block inoculum. Single and mixture conidial suspensions 1×106 of T4RH and T8R were applied to the Ganoderma-inoculated plants. It was found that T4RH, T8R, and mixed Trichoderma treatments have significantly lower disease incidence, disease severity index, area under disease progress curve, and percentage of necrotic primary roots as compared to the positive control. The disease reduction was up to 57.70% and 43.86% when plants were treated with T4RH and T8R, respectively. Additionally, the Trichoderma treatment recorded significantly higher chlorophyll content, plant height, bole diameter, and number of fronds as compared to the positive control. The findings from this study suggested that T. virens T4RH and T. asperellum T8R have the potential to be used as promising BCAs against G. boninense.